Polyisocyanate composition, resin composition, cured resin product, cured resin film, adhesive resin composition, and surface protective film

By using a polyisocyanate composition and a polymer containing crosslinkable functional groups, the problems of poor follow-up ability, poor quick drying and peeling properties in the prior art are solved, and an efficient surface protection effect is achieved.

CN119613658APending Publication Date: 2025-03-14ASAHI KASEI KOGYO KABUSHIKI KAISHA

Patent Information

Application Number
CN202411267390.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-12
Filing Date
2024-09-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to obtain a surface protective film that is good in curved surfaces or concave convex areas, has quick drying properties, and is easy to peel, and does not contaminate the adherent during peeling.

Method used

A polyisocyanate composition derived from free aliphatic bis(tri) isocyanate and alicyclic bis(tri) isocyanate and polyol is used to form a resin composition and a surface protective film.

Benefits of technology

Good follow-up, quick drying and peeling properties in curved surfaces or concave and concave areas are achieved, contamination caused by adhesive during peeling is reduced, and is suitable for surface protection such as optical components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005037545350000251
    Figure BDA0005037545350000251
  • Figure BDA0005037545350000311
    Figure BDA0005037545350000311
  • Figure BDA0005037545350000321
    Figure BDA0005037545350000321
Patent Text Reader

Abstract

Provided are a polyisocyanate composition, a resin composition, a cured resin product, a cured resin film, an adhesive resin composition, and a surface protective film, which have good adhesiveness and peelability when made into a surface protective film, and which have improved contamination properties due to an adhesive during peeling. The invention also provides the polyisocyanate composition, the resin composition, the cured resin product, the cured resin film, the adhesive resin composition, and the surface protective film. The present invention is a polyisocyanate derived from at least one di (tri) isocyanate (b1) selected from the group consisting of aliphatic di (tri) isocyanates and alicyclic di (tri) isocyanates, and a di-or higher-functional polyol (b2) having a number average molecular weight of 250-1000 (inclusive), the ratio NCO / OH of the molar amount of isocyanate groups in the di ((III)) isocyanate (b1) to the total molar amount of hydroxyl groups in the polyol (b2) is 2-30, an isocyanurate group is included, the average number of isocyanate functional groups is 5.1-7.0, and the weight-average molecular weight (Mw) is 4000-43000.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyisocyanate composition, a resin composition, a resin cured product, a resin cured film, an adhesive resin composition and a surface protection film. Background Art

[0002] In recent years, due to the shortage of manpower and the need for energy saving, quick-drying and high-curing polyisocyanates are sought. In addition, the structures of various highly functional equipment, automobiles, and buildings are becoming more complex, and the demand for applications in curved surfaces or parts that require stretching is gradually increasing. We are seeking to meet these needs.

[0003] For example, the demand for displays such as flexible displays and foldable displays has been rapidly increasing in recent years. Along with this, it is expected that the demand for coatings, plastics, adhesives, pressure-sensitive adhesives, and surface protection films that can follow curved surfaces will also increase.

[0004] For example, Patent Document 1 discloses an adhesive composition comprising: a (meth) acrylic polymer having a hydroxyl group and an acid value of 0 mgKOH / g or more and less than 16 mgKOH / g, a (meth) acrylic oligomer containing an alkylene oxide chain and an acid value of 0.1 mgKOH / g or more and 40 mgKOH / g or less, a polyether-modified silicone having a reactive group, a polyisocyanate compound as a crosslinking agent, and an ionic compound. It is also disclosed that: according to the adhesive composition, an optical component surface protection film that can achieve both antistatic properties and low contamination to the adherend at a high level can be obtained.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2017-128636 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] However, there is a demand for a PSA composition that can provide a surface protection film that has better conformability to curved surfaces or uneven surfaces than the techniques described in Patent Document 1, etc., dries quickly, is easy to peel, and reduces adherend contamination by the PSA during peeling.

[0010] The present invention has been made in view of the above circumstances, and provides a polyisocyanate composition which has good adhesion and peeling properties when made into a surface protection film and has improved contamination caused by the adhesive during peeling, as well as a resin composition, a resin cured product, a resin cured film, an adhesive resin composition and a surface protection film obtained by using the above polyisocyanate composition.

[0011] Solutions for solving problems

[0012] That is, the present invention includes the following aspects.

[0013] (1) A polyisocyanate composition, which is a polyisocyanate derived from at least one di(tri)isocyanate (b1) selected from the group consisting of aliphatic di(tri)isocyanates and alicyclic di(tri)isocyanates and a difunctional or higher polyol (b2) having a number average molecular weight of 250 or more and 1000 or less, wherein the ratio (NCO / OH) of the molar amount of isocyanate groups of the di(tri)isocyanate (b1) to the total molar amount of hydroxyl groups of the polyol (b2) is 2 or more and 30 or less, the polyisocyanate composition contains isocyanurate groups, has an average isocyanate functional group number of 5.1 or more and 7.0 or less, and has a weight average molecular weight Mw of 4000 or more and 43000 or less.

[0014] (2) The polyisocyanate composition according to (1), wherein the polyisocyanate has an isocyanate group content (NCO%) of 13.5% by mass or more and 18.3% by mass or less in a state without containing a solvent.

[0015] (3) The polyisocyanate composition according to (1) or (2), wherein the polyisocyanate contains an allophanate group.

[0016] (4) The polyisocyanate composition according to any one of (1) to (3), wherein the polyisocyanate contains an allophanate group and a urethane group.

[0017] (5) The polyisocyanate composition according to any one of (1) to (4), wherein the polyol (b2) contains at least one polyester polyol.

[0018] (6) The polyisocyanate composition according to any one of (1) to (5), wherein the polyol (b2) comprises at least one polycaprolactone polyol.

[0019] (7) The polyisocyanate composition according to any one of (1) to (6), wherein the polyol (b2) comprises at least one trifunctional or higher and tetrafunctional or lower polycaprolactone polyol.

[0020] (8) A resin composition comprising the polyisocyanate composition according to any one of (1) to (7) and a compound having a crosslinkable functional group.

[0021] (9) The resin composition according to (8), wherein the compound containing a crosslinkable functional group contains a hydroxyl group, an epoxy group, an oxetanyl group, a carboxyl group, an amino group, or a thiol group.

[0022] (10) A cured resin obtained by curing the resin composition according to (8) or (9) by light, electron beams or heat.

[0023] (11) A cured resin film, comprising the cured resin material according to (10), wherein the cured resin film has a Koenig hardness at 23° C. of 20 times or more and 150 times or less and a maximum stress in a tensile test of 10 MPa or more.

[0024] (12) An adhesive resin composition comprising the polyisocyanate composition described in any one of (1) to (7) and a polymer containing a crosslinkable functional group, wherein the glass transition temperature Tg of the polymer containing a crosslinkable functional group is greater than -75.0°C and less than 0.0°C, and the content of the polyisocyanate composition is greater than 0.01 parts by mass and less than 15.0 parts by mass relative to 100 parts by mass of the polymer containing a crosslinkable functional group.

[0025] (13) An adhesive resin composition according to (12), wherein the polymer containing a crosslinkable functional group is an acrylic polymer (A1) or a urethane polymer (A2), and the acrylic polymer (A1) is obtained by copolymerizing a monomer containing a crosslinkable functional group and a (meth)acrylate monomer having 1 to 18 carbon atoms at the end of the ester group.

[0026] (14) The adhesive resin composition according to (13), wherein the content of the structural unit derived from the monomer containing a crosslinkable functional group is 0.01 mass % or more and 25 mass % or less based on the total mass of the polymer containing a crosslinkable functional group.

[0027] (15) The adhesive resin composition according to any one of (12) to (14), wherein the weight average molecular weight of the polymer containing a crosslinkable functional group is 2.0×10 5 Above and 2.5×10 6 the following.

[0028] (16) The adhesive resin composition according to (12) to (15), wherein the crosslinkable functional group-containing polymer contains one or more selected from the group consisting of a hydroxyl group, an epoxy group, an oxetanyl group, a carboxyl group, an amino group, or a thiol group.

[0029] (17) A surface protection film comprising a plastic film and an adhesive layer on one or both surfaces of the plastic film, wherein the adhesive layer is a cured product of the adhesive resin composition according to any one of (12) to (16).

[0030] (18) The surface protection film according to (17), wherein the thickness of the adhesive layer is 1 μm or more and 1000 μm or less.

[0031] (19) A surface protection film according to (17) or (18), wherein the gel fraction calculated as follows is 90.0 mass % or more and 100.0 mass % or less: the adhesive resin composition is applied onto a release-treated polyethylene terephthalate film having a thickness of 38 μm, dried at 136°C for 3 minutes to cure, and then stored at 23°C, 50% RH for 7 days; the adhesive layer having a thickness of 20 μm thus obtained is peeled off from the release film, stored at 23°C, 50% RH for 7 days, and then wrapped with a mesh sheet, immersed in ethyl acetate at 23°C for 1 week, taken out, and then dried at 120°C for 2 hours, and the gel fraction is calculated.

[0032] (20) The surface protection film according to any one of (17) to (19), wherein the Young's modulus in a tensile test conducted as follows is 0.05 N / mm 2 Above and 0.60N / mm 2 The tensile test is carried out as follows: the adhesive resin composition is coated on a polyethylene terephthalate film having a thickness of 38 μm and subjected to a peeling treatment, and after being cured by drying at 136° C. for 3 minutes, it is stored at 23° C. and 50% RH for 7 days. The adhesive layer having a thickness of 20 μm thus obtained is laminated in a manner to have a thickness of 200 μm, cut into a layer having a width of 10 mm and a length of 40 mm, and then peeled off from the polyethylene terephthalate film having been subjected to a peeling treatment. The peeled adhesive layer is set in a tensile testing machine in a manner to have a chuck distance of 10 mm, and the tensile test is carried out at a speed of 300 mm / min at 23° C.

[0033] (21) A surface protection film according to any one of (17) to (20), wherein the 180 degree peel adhesion measured as follows is greater than or equal to 0.02 N / 25 mm and less than or equal to 2.50 N / 25 mm: the adhesive resin composition is coated on a polyethylene terephthalate film having a thickness of 25 μm, dried at 136°C for 3 minutes to cure it, and then stored at 23°C and 50% RH for 7 days. The surface protection film having an adhesive layer having a thickness of 20 μm, a width of 25 mm and a length of 100 mm thus obtained is adhered to glass as an adherend, and is reciprocated and pressed once using a 2 kg roller. After aging at 23°C for 30 minutes, the 180 degree peel adhesion is measured at 23°C and a speed of 300 mm / min.

[0034] Effects of the Invention

[0035] According to the present embodiment, there can be provided a resin cured product having excellent quick-drying properties, hardness and strength, an adhesive composition having excellent quick-drying properties and excellent releasability, a polyisocyanate composition having good followability to curved surfaces or uneven surfaces when made into a surface protection film, good adhesion and releasability, and improved contamination of the adherend by the adhesive during peeling, as well as a resin composition, a resin cured product, a resin cured film, an adhesive resin composition and a surface protection film obtained using the above-mentioned polyisocyanate composition. DETAILED DESCRIPTION

[0036] Hereinafter, a method for implementing the present invention (hereinafter referred to as "this embodiment") will be described in detail. The following embodiment is an example for illustrating the present invention, and the present invention is not limited to the following embodiment. The present invention can be implemented by appropriately modifying the scope of the present invention.

[0037] The polyisocyanate composition of this embodiment is preferably used for a quick-drying resin composition, a resin cured product, a resin cured film, a coating composition, and an adhesive resin composition. The most preferred embodiment of this embodiment is an adhesive resin composition for a surface protection film, which can obtain a surface protection film having good followability to curved surfaces or uneven surfaces, good quick-drying properties, good adhesion and peeling properties, and improved contamination of the adherend by the adhesive during peeling.

[0038] Before describing the polyisocyanate composition of the present embodiment, a polymer containing a crosslinkable functional group suitable for the adhesive resin composition will be described. The polyisocyanate composition is a polyisocyanate that becomes a crosslinking agent component (B) of the polymer containing a crosslinkable functional group.

[0039] <Polymer containing cross-linkable functional group>

[0040] As the polymer containing a crosslinkable functional group, any polymer containing a crosslinkable functional group capable of reacting with the isocyanate group of the above-mentioned polyisocyanate can be used. As the crosslinkable functional group, it is a functional group capable of forming a crosslinked structure with the crosslinking agent component (B), specifically, it is preferred to contain one or more selected from the group consisting of, for example, a hydroxyl group, an epoxy group, an oxetanyl group, a carboxyl group, an amino group or a thiol group, wherein a hydroxyl group, an epoxy group or a carboxyl group is preferred, and a hydroxyl group is more preferred.

[0041] The polymer containing a crosslinkable functional group is obtained by polymerizing a monomer containing a crosslinkable functional group. In the adhesive resin composition, the glass transition temperature Tg of the polymer containing a crosslinkable functional group is preferably -75.0°C or higher and 0.0°C or lower.

[0042] The content of the structural unit derived from the monomer containing crosslinkable functional groups is preferably 0.01% by mass or more and 25% by mass or less relative to the total mass of the polymer (A) containing crosslinkable functional groups, more preferably 0.1% by mass or more and 20% by mass or less, further preferably 0.5% by mass or more and 18% by mass or less, and particularly preferably 0.5% by mass or more and 17% by mass or less. By making the content of the structural unit derived from the monomer containing crosslinkable functional groups within the above numerical range, it is possible to obtain a surface protective film with good adhesion and peelability, and improved contamination caused by the adhesive when peeling. The content of the structural unit derived from the monomer containing crosslinkable functional groups can be calculated according to the compounding amount of the monomer containing crosslinkable functional groups used, for example, when manufacturing a polymer containing crosslinkable functional groups.

[0043] The polymer (A) containing a crosslinkable functional group is preferably an acrylic polymer (A1) obtained by copolymerizing a monomer containing a crosslinkable functional group with a (meth)acrylate monomer having 1 to 18 carbon atoms at the end of the ester group and having a glass transition temperature Tg of -75.0°C to 0.0°C, or a urethane polymer (A2) having a glass transition temperature Tg of -75.0°C to 0.0°C.

[0044] In addition, as the polymer (A) containing a crosslinkable functional group, it is more preferable to be an acrylic polymer (A1) obtained by copolymerizing a monomer containing a crosslinkable functional group and a (meth)acrylate monomer having 1 to 18 carbon atoms at the end of the ester group and having a glass transition temperature Tg of -75.0°C to 0.0°C.

[0045] [Acrylic polymer (A1)]

[0046] The acrylic polymer (A1) contains one or more polymerizable (meth)acrylic monomer units having a crosslinkable functional group as a monomer unit containing a crosslinkable functional group. As the crosslinkable functional group, it is preferred to contain a hydroxyl group, an epoxy group, an oxetanyl group, a carboxyl group, an amino group or a thiol group, more preferably a hydroxyl group, a carboxyl group or an epoxy group, and even more preferably a hydroxyl group.

[0047] The acrylic polymer (A1) may contain a crosslinkable functional group alone or in combination of two or more different types of crosslinkable functional groups. That is, the acrylic polymer may be obtained by polymerizing a polymerizable (meth)acrylic monomer having a crosslinkable functional group alone or by copolymerizing two or more polymerizable (meth)acrylic monomers having different types of crosslinkable functional groups in combination.

[0048] The acrylic polymer (A1) preferably contains, in addition to the polymerizable (meth)acrylic monomer unit having a crosslinkable functional group, one or more (meth)acrylic acid ester monomer units having 1 to 18 carbon atoms at the terminal ester group.

[0049] That is, the acrylic polymer (A1) may be obtained by copolymerizing one or more polymerizable (meth)acrylic monomers having a crosslinkable functional group and one or more (meth)acrylate monomers having an ester group terminal with carbon atoms of 1 to 18. The (meth)acrylate monomer may or may not have a crosslinkable functional group, but preferably does not have one.

[0050] The number of carbon atoms at the terminal ester group of the (meth)acrylate monomer is preferably 1 or more and 18 or less.

[0051] Examples of the polymerizable (meth)acrylic monomer having a crosslinkable functional group include the monomers (i) to (v) below. These may be used alone or in combination of two or more.

[0052] (i) Acrylic acid esters having a hydroxyl group such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, 4-hydroxybutyl acrylate, 6-hydroxyhexyl acrylate, and 8-hydroxyoctyl acrylate.

[0053] (ii) Methacrylic acid esters having a hydroxyl group such as 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl methacrylate, and 8-hydroxyoctyl methacrylate.

[0054] (iii) (meth)acrylates having a polyhydric hydroxyl group, such as monoacrylate or monomethacrylate of glycerol and monoacrylate or monomethacrylate of trimethylolpropane.

[0055] (iv) Unsaturated carboxylic acids such as acrylic acid and methacrylic acid.

[0056] (v) (Meth)acrylates having an epoxy group such as glycidyl methacrylate.

[0057] Examples of the (meth)acrylate monomer having 1 to 18 carbon atoms at the end of the ester group include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, and (meth)acrylate. (Meth)acrylates such as isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (lauryl (meth)acrylate), tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, benzyl (meth)acrylate, and cyclohexyl (meth)acrylate. These may be used alone or in combination of two or more.

[0058] The acrylic polymer (A1) may contain other monomer units other than the above-mentioned (meth)acrylate monomers in addition to the polymerizable (meth)acrylic monomer units having a crosslinkable functional group.

[0059] That is, the acrylic polymer (A1) is obtained by polymerizing one or more polymerizable (meth) acrylic monomers having a crosslinkable functional group, or by copolymerizing one or more polymerizable (meth) acrylic monomers having a crosslinkable functional group with one or more other monomers. The other monomers may or may not have a crosslinkable functional group, but preferably do not have a crosslinkable functional group.

[0060] Examples of other monomers include monomers shown in (i) to (ii) below. These monomers may be used alone or in combination of two or more.

[0061] (i) Unsaturated amides such as (meth)acrylamide, N-methylolacrylamide, diacetoneacrylamide, and dimethylaminopropylacrylamide.

[0062] (ii) Styrene, vinyltoluene, vinyl acetate, (meth)acrylonitrile, N-vinylpyrrolidone, N-vinylcaprolactam, acryloylmorpholine, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate.

[0063] Furthermore, as other monomers copolymerizable with the polymerizable (meth)acrylic monomer having a crosslinkable functional group, polymerizable ultraviolet stabilizing monomers disclosed in JP-A-1-261409 (reference 1) and JP-A-3-006273 (reference 2) can be used.

[0064] Specific examples of the polymerizable UV-stable monomer include 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-crotonyl-4-crotonyloxy-2,2,6,6-tetramethylpiperidine, and 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone.

[0065] For example, the acrylic polymer can be obtained by solution polymerizing the above-mentioned monomer components in the presence of a known radical polymerization initiator such as a peroxide or an azo compound, and diluting the mixture with an organic solvent or the like as necessary.

[0066] In the case of obtaining an acrylic polymer of a water-based matrix, it can be produced by a known method such as a method of subjecting an ethylenically unsaturated compound to solution polymerization and converting it into an aqueous layer, emulsion polymerization, etc. In this case, water solubility or water dispersibility can be imparted by neutralizing the acidic part of a carboxylic acid-containing monomer such as acrylic acid or methacrylic acid and / or a sulfonic acid-containing monomer with amines and / or ammonia.

[0067] The weight average molecular weight Mw(A) of the polymer (A) containing a crosslinkable functional group is preferably 2.0×10 5 Above and 2.5×10 6 Below, more preferably 3.0×10 5 Above and 2.0×10 6 Below, more preferably 3.5×10 5 Above and 1.8×10 6 , particularly preferably 3.7×10 5 Above and 1.5×10 6 By making the weight average molecular weight of the polymer (A) containing a crosslinkable functional group within the above range, a surface protection film having good wettability, good adhesion, easy peeling, and improved contamination caused by the adhesive during peeling can be obtained. The weight average molecular weight Mw of the polymer (A) containing a crosslinkable functional group can be measured using, for example, the method described in the examples described below.

[0068] <Polyisocyanate composition>

[0069] The polyisocyanate composition of the present embodiment includes the following polyisocyanate composition, wherein the polyisocyanate composition is a polyisocyanate derived from at least one di(tri)isocyanate (b1) selected from the group consisting of aliphatic di(tri)isocyanates and alicyclic di(tri)isocyanates and a difunctional or higher polyol (b2) having a number average molecular weight of 250 or more and 1000 or less, the ratio NCO / OH of the molar amount of isocyanate groups of the aforementioned di(tri)isocyanate (b1) to the total molar amount of hydroxyl groups of the aforementioned polyol (b2) is 2 or more and 30 or less, the polyisocyanate composition contains isocyanurate groups, the average number of isocyanate functional groups is 5.1 or more and 7.0 or less, and the weight average molecular weight Mw is 4000 or more and 43000 or less.

[0070] The diisocyanate (triisocyanate) is at least one selected from the group consisting of diisocyanates and triisocyanates. The polyisocyanate derived from the aliphatic or alicyclic diisocyanate (triisocyanate) (b1) and the difunctional or higher polyol (b2) is an aliphatic or alicyclic polyisocyanate.

[0071] The weight average molecular weight Mw(b) of the aliphatic or alicyclic polyisocyanate is 4000 to 43000, preferably 4400 to 43000, more preferably 4500 to 42000, further preferably 4500 to 40000, further preferably 4500 to 35000, further preferably 4500 to 32000, further preferably 4500 to 28000, further preferably 4500 to 23000, further preferably 4500 to 20000, further preferably 4500 to 18000, particularly preferably 4500 to 16000. By making the weight average molecular weight Mw(b) of the aliphatic or alicyclic polyisocyanate within the above numerical range, it is possible to obtain a surface protection film having an adhesive layer which has good storage stability, good wettability, good adhesion, quick drying, curing properties, better adhesion, excellent unevenness followability, easier peeling, and further improved contamination resistance of the polyisocyanate.

[0072] The Mw(b) of the aliphatic or alicyclic polyisocyanate is a weight average molecular weight based on polystyrene measured by GPC.

[0073] The average number of isocyanate functional groups of the aliphatic or alicyclic polyisocyanate (also referred to as the "average number of isocyanate groups") is 5.1 or more and 7.0 or less, more preferably 5.1 or more and 6.9 or less, more preferably 5.1 or more and 6.8 or less, more preferably 5.1 or more and 6.7 or less, particularly preferably 5.2 or more and 6.6 or less, and most preferably 5.5 or more and 6.6 or less. By making the average number of isocyanate groups of the aliphatic or alicyclic polyisocyanate within the above numerical range, a surface protective film having an adhesive layer with good wettability, good adhesion, quick drying, curing, and adhesion, easier peeling, and further improved contamination can be obtained.

[0074] The average number of isocyanate groups (fn) of an aliphatic or alicyclic polyisocyanate can be calculated using the following formula. In the following formula, "Mn" represents the number average molecular weight of the aliphatic or alicyclic polyisocyanate, and "NCO%" represents the isocyanate group content of the aliphatic or alicyclic polyisocyanate. The number average molecular weight Mn of an aliphatic or alicyclic polyisocyanate is a weight average molecular weight based on a polystyrene standard determined by GPC. The method for determining NCO% is described below.

[0075] [fn] = [Mn] × [NCO%] / 4200

[0076] The ratio NCO / OH of the molar amount of the isocyanate group of the di(tri)isocyanate (b1) to the total molar amount of the hydroxyl group of the polyol (b2) is preferably 2 or more and 30 or less, more preferably 3 or more and 28 or less, further preferably 4 or more and 27 or less, and particularly preferably 5 or more and 25 or less. By making the NCO / OH ratio within the above numerical range, a surface protection film having an adhesive layer having good wettability, good adhesion, quick drying, curing, and adhesion, easier peeling, and improved contamination resistance can be obtained.

[0077] The aliphatic or alicyclic polyisocyanate may have at least one structure selected from the group consisting of an allophanate structure, a uretdione structure, an iminooxadiazinedione structure, an isocyanurate structure, a urea structure, a carbamate structure, and a biuret structure. Among them, it is preferred to have at least one structure selected from the group consisting of a carbamate structure, an allophanate structure, a biuret structure, a urea structure, and an isocyanurate group.

[0078] The polyisocyanate contains an isocyanurate group. Furthermore, the polyisocyanate preferably contains an allophanate group, and more preferably contains an allophanate group and a urethane group.

[0079] [Di(tri)isocyanate (b1)]

[0080] The diisocyanate (b1) is at least one selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates, preferably at least one selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates. The diisocyanate (b1) is used as an isocyanate monomer in the production of polyisocyanates.

[0081] The aliphatic diisocyanate is not limited to the following aliphatic diisocyanates, and examples thereof include 1,4-diisocyanatobutane, 1,5-diisocyanatopentane (hereinafter sometimes abbreviated as "PDI"), (2,6-diisocyanato)ethylhexanoate, 1,6-diisocyanatohexane (hereinafter sometimes abbreviated as "HDI"), 1,7-diisocyanatoheptane, 1,8-diisocyanatooctane, 1,9-diisocyanatononane, 1,12-diisocyanatododecane, 2,2,4-trimethyl-1,6-diisocyanatohexane, and 2,4,4-trimethyl-1,6-diisocyanatohexane. These aliphatic diisocyanates may be used alone or in combination of two or more.

[0082] The alicyclic diisocyanate is not limited to the following substances, and examples thereof include 1,3-bis(isocyanatomethyl)cyclohexane or 1,4-bis(isocyanatomethyl)cyclohexane (hereinafter sometimes referred to as "hydrogenated XDI"), 1,3-diisocyanatocyclohexane or 1,4-diisocyanatocyclohexane, 3,5,5-trimethyl1-isocyanato-3-(isocyanatomethyl)cyclohexane (hereinafter sometimes referred to as "IPDI"), 4-4'-diisocyanato-dicyclohexylmethane (hereinafter sometimes referred to as "hydrogenated MDI"), 2,5-diisocyanatomethylnorbornane or 2,6-diisocyanatomethylnorbornane, etc. These alicyclic diisocyanates may be used alone or in combination of two or more.

[0083] These aliphatic diisocyanates and alicyclic diisocyanates may be used alone, or two or more of these aliphatic diisocyanates and alicyclic diisocyanates may be used in combination.

[0084] In addition, from the viewpoint of flexibility, the mass ratio of the alicyclic polyisocyanate to the aliphatic diisocyanate is preferably 0 / 100 or more and 30 / 70 or less.

[0085] Among them, the diisocyanate is preferably HDI, 1,4-diisocyanatobutane, PDI, 1,7-diisocyanatoheptane, 1,8-diisocyanatooctane, IPDI, hydrogenated XDI or hydrogenated MDI, more preferably PDI, HDI or IPDI, and even more preferably PDI and HDI.

[0086] In the production of polyisocyanate, in addition to the above-mentioned diisocyanate, an isocyanate monomer as shown below can be further used.

[0087] (1) Aromatic diisocyanates such as diphenylmethane-4,4'-diisocyanate (MDI), 1,5-naphthalene diisocyanate, toluene diisocyanate (TDI), xylylene diisocyanate, and tetramethyl metaxylylene diisocyanate (TMXDI).

[0088] (2) Triisocyanates such as 4-isocyanatemethyl-1,8-octamethylene diisocyanate (hereinafter sometimes referred to as "NTI"), 1,3,6-hexamethylene triisocyanate (hereinafter sometimes referred to as "HTI"), 2-isocyanatoglutaric acid bis(2-isocyanatoethyl) ester (hereinafter sometimes referred to as "GTI"), and lysine triisocyanate (hereinafter sometimes referred to as "LTI").

[0089] [Polyol (b2)]

[0090] The polyol (b2) is a difunctional or higher polyol (b2). The number average molecular weight of the polyol (b2) is 250 to 1000, preferably 250 to 900, more preferably 250 to 860, more preferably 270 to 860, most preferably 270 to 550.

[0091] As the polyol (b2), it is preferred to be at least one trifunctional polyol (triol) selected from the group consisting of polyester polyols, polyether polyols, epoxy polyols, polyolefin polyols and polycarbonate polyols, more preferably at least one polyester polyol, more preferably at least one polycaprolactone polyol, further preferably a trifunctional polyester polyol, and most preferably a trifunctional polycaprolactone polyol.

[0092] Examples of the bifunctional polyester polyol include polyester polyols of (1) or (2) below.

[0093] (1) A polyester polyol obtained by a condensation reaction of a single dibasic acid or a mixture of two or more dibasic acids with a single diol or a mixture of two or more diols.

[0094] (2) Polycaprolactone polyol obtained by ring-opening polymerization of ε-caprolactone using a diol.

[0095] Examples of the dibasic acid include carboxylic acids such as succinic acid, adipic acid, dimer acid, maleic anhydride, phthalic anhydride, isophthalic acid, terephthalic acid, and 1,4-cyclohexanedicarboxylic acid.

[0096] Examples of the diol include ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, trimethylpentanediol, and cyclohexanediol.

[0097] Among them, as the bifunctional polyester polyol, bifunctional polycaprolactone polyol is preferred.

[0098] As the polyol (b2), a trifunctional or higher polyol is preferably a trifunctional or higher and decafunctional or lower polyol, a trifunctional or higher and heptafunctional or lower polyol is more preferably a trifunctional or higher and pentafunctional or lower polyol is further preferably a trifunctional or higher and tetrafunctional or lower polyol is particularly preferably, and a trifunctional polyol (triol) is most preferably.

[0099] The trifunctional polyol (triol) is preferably at least one trifunctional polyol (triol) selected from the group consisting of polyester polyols, polyether polyols, epoxy polyols, polyolefin polyols and polycarbonate polyols, more preferably a trifunctional polyether polyol or polyester polyol, and still more preferably a trifunctional polyester polyol.

[0100] Examples of the trifunctional polyester polyol include polyester polyols of (1) or (2) below.

[0101] (1) A polyester polyol obtained by a condensation reaction of a single dibasic acid or a mixture of two or more dibasic acids with a single triol or a mixture of two or more triols.

[0102] (2) Polycaprolactone polyol obtained by ring-opening polymerization of ε-caprolactone using a triol.

[0103] Examples of the dibasic acid include carboxylic acids such as succinic acid, adipic acid, dimer acid, maleic anhydride, phthalic anhydride, isophthalic acid, terephthalic acid, and 1,4-cyclohexanedicarboxylic acid.

[0104] Examples of the triol include trimethylolpropane, glycerin, pentaerythritol, 2-methylolpropanediol, and ethoxylated trimethylolpropane.

[0105] Among them, as the trifunctional polyester polyol, trifunctional polycaprolactone polyol is preferred.

[0106] Examples of commercially available trifunctional polycaprolactone polyols include "PLACCEL 303" (number average molecular weight: 310), "PLACCEL 305" (number average molecular weight: 550), "PLACCEL 308" (number average molecular weight: 850), "PLACCEL 312" (number average molecular weight: 1250), and "PLACCEL 320" (number average molecular weight: 2000) manufactured by Daicel Corporation; OD-X-2733 (number average molecular weight: 300), OD-X-2735 (number average molecular weight: 550), and OD-X-2742C (number average molecular weight: 850) manufactured by DIC Corporation;

[0107] The difunctional or higher polyol (b2) preferably contains at least one polycaprolactone polyol, and more preferably contains at least one trifunctional or higher and tetrafunctional or lower polycaprolactone polyol.

[0108] The trifunctional or higher-functional but lower-functional polycaprolactone polyol is obtained by, for example, ring-opening polymerization of ε-caprolactone with a trivalent or higher-functional but lower-functional alcohol.

[0109] [Method for producing polyisocyanate composition]

[0110] The aliphatic or alicyclic polyisocyanate is obtained by reacting the above-mentioned diisocyanate (b1) with the polyol (b2).

[0111] [Physical properties of polyisocyanates]

[0112] The isocyanate group content (NCO group content) of the polyisocyanate composition is more preferably 13.0% to 18.3% (in terms of mass%), more preferably 13.5% to 18.2% (in terms of mass%), more preferably 13.7% to 18.0% (in terms of mass%), more preferably 13.7% to 18.0% (in terms of mass%), more preferably 14.0% to 18.0% (in terms of mass%), more preferably 14.5% to 18.0% (in terms of mass%), more preferably 14.8% to 18.0% (in terms of mass%), and particularly preferably 15.0% to 17.9% (in terms of mass%).

[0113] The NCO group content can be determined, for example, by reacting the isocyanate groups in the polyisocyanate composition with an excess of amine (such as dibutylamine) and back-titrating the remaining amine with an acid such as hydrochloric acid.

[0114] The isocyanate group content (NCO%) of the polyisocyanate after removing the solvent is preferably 13.0% to 18.3%, and more preferably 13.5% to 18.3%.

[0115] <Resin composition>

[0116] The resin composition of the present embodiment includes the polyisocyanate composition and a crosslinkable functional group-containing compound. The crosslinkable functional group-containing compound preferably contains a hydroxyl group, an epoxy group, an oxetanyl group, a carboxyl group, an amino group, or a thiol group.

[0117] The resin composition of the present embodiment can be cured by light, electron beams, or heat to obtain a cured resin. Examples of the light include ultraviolet rays and visible rays.

[0118] <Resin Cured Product and Resin Cured Film>

[0119] As a cured resin, it is obtained by applying a resin composition on a substrate and curing it. The film thickness of the resulting cured resin film can be appropriately determined according to the intended use, preferably 1 μm or more and 1000 μm or less, more preferably 2 μm or more and 900 μm or less, further preferably 3 μm or more and 800 μm or less, preferably 4 μm or more and 700 μm or less, more preferably 4 μm or more and 600 μm or less, more preferably 4 μm or more and 500 μm or less, more preferably 4 μm or more and 400 μm or less, more preferably 4 μm or more and 300 μm or less, more preferably 4 μm or more and 200 μm or less, more preferably 4 μm or more and 100 μm or less, and most preferably 4 μm or more and 50 μm or less.

[0120] Preferably, the following resin cured film is used: the above-mentioned polyisocyanate and the compound containing a crosslinking functional group are applied on glass, and the cured film with a film thickness of 50 μm formed after being stored at 23° C. and 65% RH for 168 hours has a Koenig hardness of 20 times or more and 150 times or less at 23° C. By making the Koenig hardness below the above-mentioned upper limit and above the lower limit, it has appropriate hardness, strength, and flexibility, and excellent curability. The maximum stress of the above-mentioned resin cured film in a tensile test is preferably 10 MPa or more.

[0121] <Adhesive resin composition>

[0122] The adhesive resin composition of the present embodiment comprises the polyisocyanate composition and a polymer containing a crosslinkable functional group having a glass transition temperature Tg of -75.0°C or higher and 0.0°C or lower. The content of the polyisocyanate composition is preferably 0.01 parts by mass or higher and 15.0 parts by mass or lower relative to 100 parts by mass of the polymer containing a crosslinkable functional group. The adhesive resin composition is suitable as an adhesive resin composition for a surface protection film.

[0123] [Isocyanate group / crosslinking functional group]

[0124] The molar ratio of the isocyanate group of the crosslinking agent component (B) contained in the adhesive resin composition for the surface protection film of the present embodiment to the crosslinking functional group (especially hydroxyl group) of the polymer (A) containing the crosslinking functional group (molar ratio of isocyanate group / crosslinking functional group) is determined according to the desired physical properties of the surface protection film and is generally greater than 0.005 and less than 50.

[0125] <Other ingredients>

[0126] The adhesive resin composition for a surface protection film of the present embodiment may further contain other additives.

[0127] Examples of other additives include curing agents other than the crosslinking agent component (B) that can react with the polymer (A) containing a crosslinkable functional group, curing catalysts, solvents, pigments (extender pigments, coloring pigments, metallic pigments, etc.), tackifying resins, photopolymerization initiators, ultraviolet absorbers, light stabilizers, free radical stabilizers, anti-yellowing agents for suppressing coloration during the sticking process, coating surface regulators, flow regulators, pigment dispersants, defoamers, thickeners, film-forming aids, antistatic agents, and the like.

[0128] Examples of the curing agent include melamine resins, urea resins, epoxy group-containing compounds or resins, carboxyl group-containing compounds or resins, acid anhydrides, alkoxysilyl group-containing compounds or resins, and hydrazide compounds.

[0129] The curing catalyst may be a basic compound or a Lewis acid compound.

[0130] Examples of the basic compound include metal hydroxides, metal alkoxides, metal carboxylates, acetylacetonate metal salts, hydroxides of onium salts, carboxylates of onium salts, halides of onium salts, metal salts of active methylene compounds, onium salts of active methylene compounds, aminosilanes, amines, phosphines, etc. The onium salt is preferably an ammonium salt, a phosphonium salt or a sulfonium salt.

[0131] Examples of the Lewis acidic compound include organic tin compounds, organic zinc compounds, organic titanium compounds, and organic zirconium compounds.

[0132] Examples of the solvent include 1-methylpyrrolidone, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, dipropylene glycol monomethyl ether, propylene glycol monomethyl ether, 3-methoxy-3-methyl-1-butanol, ethylene glycol diethyl ether, diethylene glycol diethyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dipropylene glycol dimethyl ether (DPDM), propylene glycol dimethyl ether, methyl ethyl ketone, Acetone, methyl isobutyl ketone, propylene glycol monomethyl ether acetate, ethanol, methanol, isopropanol, 1-propanol, isobutanol, 1-butanol, tert-butanol, 2-ethylhexanol, cyclohexanol, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, ethyl acetate, isopropyl acetate, butyl acetate, toluene, xylene, pentane, isopentane, hexane, isohexane, cyclohexane, solvent naphtha, mineral spirits, etc. These solvents may be used alone or in combination of two or more.

[0133] In addition, as pigments (extender pigments, coloring pigments, metallic pigments, etc.), ultraviolet absorbers, light stabilizers, free radical stabilizers, anti-yellowing agents for suppressing coloration during the sticking process, coating surface regulators, flow regulators, pigment dispersants, defoamers, thickeners and film-forming aids, known substances can be appropriately selected and used.

[0134] As the antistatic agent, an alkali metal salt is preferred. Examples of the alkali metal salt include metal salts formed from lithium, sodium, and potassium. Specifically, for example, a metal salt containing Li + 、Na + , K + The cations and Cl - ,Br-,I-,BF4 - PF6 - 、SCN - 、ClO4 - CF3SO3 - 、(CF3SO2)2N - 、(C2F5SO2)2N - 、(CF3SO2)3C - The present invention relates to a metal salt composed of an anion of a cation. Among them, lithium salts such as LiBr, LiI, LiBF4, LiPF6, LiSCN, LiClO4, LiCF3SO3, Li(CF3SO2)2N, Li(C2F5SO2)2N, and Li(CF3SO2)3C are particularly preferably used. These alkali metal salts can be used alone, or two or more can be mixed and used. In order to stabilize the ionic substance, a compound containing a polyoxyalkylene structure can be added.

[0135] <Method for producing adhesive resin composition for surface protection film>

[0136] The adhesive resin composition for surface protection film can be produced by a conventionally known method. For example, a melt kneading method using a Banbury mixer, a single screw extruder, a twin screw extruder, a co-kneader, a multi-screw extruder or the like can be adopted; a method in which each component is dissolved or dispersed and mixed, and then applied to a substrate film by a coater or the like, and then the solvent is removed by heating.

[0137] In order to achieve the effect of improving lightness, flexibility and adhesion, the adhesive resin composition for surface protection film of the present embodiment can be foamed. As the foaming method, there are chemical methods, physical methods, and the use of heat-expandable microspheres. Bubbles can be distributed inside the material by adding chemical foaming agents such as inorganic foaming agents or organic foaming agents or physical foaming agents, or adding heat-expandable microspheres.

[0138] In addition, by adding a hollow filler (expanded hollow spheres), weight reduction, flexibility, and improved adhesion can be achieved.

[0139] The adhesive resin composition for the surface protection film of the present embodiment may be added with a tackifier resin for adjusting the adhesive force and the cohesive force. As the tackifier resin, for example, a rosin-based tackifier resin, a terpene-based tackifier resin, a petroleum-based tackifier resin, a styrene-based tackifier resin, etc. may be listed. These tackifier resins may be used alone or in combination of two or more. In addition, the softening point of the tackifier resin is preferably above 90° C. and below 160° C.

[0140] 《Surface protection film》

[0141] The surface protection film of the present embodiment includes a plastic film, and an adhesive layer is provided on one surface or both surfaces of the plastic film.

[0142] The adhesive layer is formed from a cured product of the adhesive resin composition for a surface protection film.

[0143] In the surface protection film of the present embodiment, the adhesive layer has good wettability, good adhesion, good unevenness followability, is easy to peel, and is less susceptible to contamination by the adhesive during peeling.

[0144] In the surface protection film of the present embodiment, the thickness of the adhesive layer can be appropriately determined according to the intended use, and is preferably from 1 μm to 1000 μm, more preferably from 2 μm to 900 μm, further preferably from 3 μm to 800 μm, more preferably from 4 μm to 700 μm, more preferably from 4 μm to 600 μm, more preferably from 4 μm to 500 μm, more preferably from 4 μm to 400 μm, more preferably from 4 μm to 300 μm, more preferably from 4 μm to 200 μm, more preferably from 4 μm to 100 μm, and most preferably from 4 μm to 50 μm.

[0145] The surface protection film of the present embodiment can be produced by, for example, applying the adhesive resin composition for a surface protection film on a substrate, drying it as necessary, and then curing it.

[0146] As a method for coating the adhesive resin composition for surface protection film on the substrate, for example, a method of coating using an applicator, a roll coater, a knife coater, a gravure coater, etc. can be cited. When drying after the above coating, for example, a heating drying method can be cited, for example, placing the obtained laminate in a dryer, for example, at a temperature of 50° C. to 150° C. for 1 minute to 30 minutes. Alternatively, as other drying methods, for example, natural drying, hot air drying, infrared drying, etc. can be cited.

[0147] The heating temperature during curing may be 70° C. or higher and 160° C. or lower, 75° C. or higher and 155° C. or lower, or 80° C. or higher and 150° C. or lower.

[0148] Regarding the adhesive layer for the surface protection film of the present embodiment, the adhesive resin composition for the surface protection film is coated on a polyethylene terephthalate film with a thickness of 38 μm and subjected to peeling treatment, and after being cured by drying at 136° C. for 3 minutes, it is stored at 23° C. and 50% RH for 7 days, and the adhesive layer with a thickness of 20 μm obtained thereby is peeled off from the peeling film, stored at 23° C. and 50% RH for 7 days, and then wrapped with a mesh sheet, immersed in ethyl acetate at 23° C. for 1 week and taken out, and then dried at 120° C. for 2 hours, and the gel fraction calculated thereby is preferably 90.0 mass % or more and 100.0 mass % or less. By making the gel fraction above the above lower limit, the curability, peelability, and residual adhesive property are more excellent.

[0149] The gel fraction referred to herein refers to the percentage of the mass of the adhesive layer for surface protection films after being immersed in ethyl acetate and then dried relative to the mass of the adhesive layer for surface protection films before being immersed in ethyl acetate.

[0150] Regarding the adhesive layer for the surface protection film of the present embodiment, the above-mentioned adhesive resin composition for the surface protection film is applied on a polyethylene terephthalate film with a thickness of 38 μm and subjected to a peeling treatment, and after being cured by drying at 136° C. for 3 minutes, it is stored for 7 days under an environment of 23° C. and 50% RH. The adhesive layer with a thickness of 20 μm thus obtained is laminated in a manner to have a thickness of 200 μm, cut into a width of 10 mm and a length of 40 mm, and then peeled off from the polyethylene terephthalate film subjected to the peeling treatment. The peeled adhesive layer is set in a tensile testing machine in a manner in which the distance between the chucks becomes 10 mm. The Young's modulus in the tensile test performed at a speed of 300 mm / min under an environment of 23° C. is preferably 0.60 N / mm 2 Below, more preferably 0.55N / mm 2 Below, more preferably 0.50 N / mm 2 Below, particularly preferably 0.47 N / mm 2 When the Young's modulus is equal to or less than the upper limit value described above, the elastic modulus is lower, and the adhesion, wettability, and followability to an adherend are more excellent.

[0151] In addition, the lower limit of the Young's modulus can be set to 0.05 N / mm, for example. 2 .

[0152] Regarding the surface protection film of the present embodiment, the above-mentioned adhesive resin composition for surface protection film is applied on a polyethylene terephthalate film having a thickness of 25 μm, and after being dried at 136° C. for 3 minutes to cure it, it is stored at 23° C. and 50% RH for 7 days. The surface protection film having an adhesive layer having a thickness of 20 μm, a width of 25 mm, and a length of 100 mm is attached to a glass as an adherend, and is reciprocated and pressed once with a 2 kg roller. After aging at 23° C. for 30 minutes, the 180-degree peeling adhesive strength measured at 23° C. and a speed of 300 mm / min is preferably 0.01 N / 25 mm or more and 2.50 N / 25 mm or less, and more preferably 0.02 N / 25 mm or more and 2.50 N / 25 mm or more. 0.02N / 25mm and below 2.40N / 25mm, more preferably 0.025N / 25mm and below 2.30N / 25mm, more preferably 0.030N / 25mm and below 2.10N / 25mm, more preferably 0.030N / 25mm and below 2.00N / 25mm, more preferably 0.030N / 25mm and below 1.70N / 25mm, more preferably 0.030N / 25mm and below 1.50N / 25mm, more preferably 0.030N / 25mm and below 1.25N / 25mm, most preferably 0.030N / 25mm and below 1.00N / 25mm. By making the 180 degree peeling adhesive force within the above numerical range, the adhesion is good, the peeling will not be too heavy, and it is easy to peel off from the adherend, which can make the peeling property better.

[0153] As described above, the surface protection film of this embodiment has good curability, good wettability, good adhesion, is easy to peel, and has improved contamination by the adhesive during peeling. Therefore, it can be suitably used as a surface protection film for optical components, for example.

[0154] Example

[0155] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited to the following examples.

[0156] [Physical properties 1]

[0157] (Glass transition temperature Tg)

[0158] Regarding the glass transition temperature of the polymer (A) containing a crosslinkable functional group, the organic solvent and water in the solution of the polymer (A) containing a crosslinkable functional group are removed under reduced pressure, followed by vacuum drying. The resulting substance is measured using a differential scanning calorimeter (DSC) measuring apparatus at a heating rate of 5°C / min, and the value obtained is used as the glass transition temperature.

[0159] [Physical Properties 2]

[0160] (Number average molecular weight and weight average molecular weight)

[0161] The number average molecular weight and the weight average molecular weight are polystyrene-based number average molecular weight and weight average molecular weight obtained by gel permeation chromatography (GPC) measurement using the following apparatus.

[0162] (Measurement conditions)

[0163] Device: HLC-802A manufactured by Tosoh Corporation

[0164] Column: Made by Tosoh Corporation, G1000HXL x 1

[0165] G2000HXL×1

[0166] G3000HXL×1

[0167] Carrier: Tetrahydrofuran

[0168] Detection method: Differential refractometer

[0169] [Physical Properties 3]

[0170] (Isocyanate group content)

[0171] First, accurately weigh more than 2g and less than 3g (Wg) of the test sample in a flask. Then, add 20mL of toluene to dissolve the test sample. Then, add 20mL of a toluene solution of di-n-butylamine at a 2N concentration and mix, and leave at room temperature for 15 minutes. Then, add 70mL of isopropanol and mix. Then, titrate the liquid with a 1N concentration of hydrochloric acid solution (factor F) in an indicator. The obtained titration value is set to V2mL. Next, the titration value obtained under the condition of no sample is set to V1ml. Next, calculate the isocyanate group content (NCO%) (mass %) of the crosslinking agent component (B) according to the following formula.

[0172] "Isocyanate group content (mass %)" = (V1-V2) × F × 42 / (W × 1000) × 100

[0173] [Physical Properties 4]

[0174] (Average number of isocyanate functional groups)

[0175] The average number of isocyanate functional groups (average number of NCO) of the crosslinking agent component (B) is calculated by the following formula. It should be noted that in the formula, "Mn" refers to the number average molecular weight, which is the value measured in the above "Physical Property 2". "NCO%" is the value calculated in the above "Physical Property 3".

[0176] "Average number of isocyanate functional groups" = (Mn x NCO% x 0.01) / 42

[0177] [Preparation of Cured Film of Polyisocyanate Composition (B) and Crosslinkable Functional Group Compound]

[0178] The polyisocyanate composition (B) and an acrylic polyol (crosslinking functional group compound) having a Tg of 15°C were mixed in a manner of NCO / OH=1, ethyl acetate was added to dilute the mixture to a concentration of 45%, and the mixture was applied on glass using an applicator. After being stored at 23°C and 65% RH for 168 hours, a cured film having a film thickness of 50 μm was obtained.

[0179] [Evaluation of Quick-Drying Property of Resin Composition of Polyisocyanate Composition (B) and Crosslinkable Functional Group Compound]

[0180] The polyisocyanate composition (B) and an acrylic polyol (crosslinking functional group compound) having a Tg of 15°C were mixed in a manner of NCO / OH=1, ethyl acetate was added, and the mixture was diluted to a concentration of 45%, and the mixture was applied to a release film using an applicator. After being stored at 23°C and 50% RH for 24 hours, a cured film having a film thickness of 50 μm was obtained. The gel fraction of the cured film was measured. The case where the gel fraction was 85% by mass or more was considered to have good curability.

[0181] [Property 5]

[0182] (Koenig hardness)

[0183] The Koenig hardness (times) of each cured film in an environment of 23° C. was measured using a Koenig hardness tester (Pendulum hardness tester manufactured by BYK Gardner).

[0184] <Evaluation method>

[0185] [Preparation of surface protection film 1 (adhesive layer)]

[0186] Each adhesive resin composition for surface protection film was applied to a 38 μm thick PET film subjected to peeling treatment using an applicator so that the thickness after drying was 20 μm, and dried at 136° C. for 3 minutes. Thereafter, the film was stored at 23° C. and 50% RH for 7 days to obtain a surface protection film 1 (adhesive layer) for measuring gel fraction and for tensile testing. During the measurement, the peeling-treated PET film was peeled off for testing.

[0187] [Preparation of Surface Protection Film 2]

[0188] Each adhesive resin composition for a surface protection film was applied onto a polyethylene terephthalate (PET) film having a thickness of 25 μm using an applicator so that the thickness after drying was 20 μm, and dried at 136° C. for 3 minutes. Thereafter, the film was stored at 23° C. and 50% RH for 7 days to obtain a surface protection film 2 for measuring 180-degree peeling adhesive strength.

[0189] [Evaluation 1]

[0190] (Gel fraction)

[0191] About 0.1 g to 0.2 g of the adhesive layer obtained by the above-mentioned "Preparation of Surface Protection Film 1" was peeled off from the release film, wrapped with a mesh sheet, immersed in ethyl acetate for 1 week, and dried at 120° C. for 2 hours. Next, the gel fraction (mass %) was calculated using the following formula.

[0192] The materials having a gel fraction of 90% by mass or more were evaluated to have good curability.

[0193] [Evaluation 2]

[0194] (Tensile test: Young's modulus)

[0195] The adhesive layer obtained by the above-mentioned "Preparation of Surface Protection Film 1" was laminated so as to have a thickness of 200 μm and cut into a width of 10 mm and a length of 40 mm. Thereafter, only the adhesive layer peeled off from the release film was placed in a tensile tester so that the distance between the chucks was 10 mm, and the Young's modulus was measured at a speed of 300 mm / min under an environment of 23°C using the tensile tester.

[0196] About Young's modulus is 0.60N / mm 2 The following materials were evaluated to have good adhesiveness and good followability to adherends.

[0197] [Evaluation 3]

[0198] (180 degree peel adhesion and stain resistance)

[0199] The surface protection film 2 obtained by the above-mentioned "Preparation of surface protection film 2" was cut into a width of 25 mm and a length of 100 mm to obtain a test piece. Next, the test piece was attached to the glass as an adherend, and a 2 kg roller was reciprocated once to press the test piece to the glass. After aging at 23°C for 30 minutes, the 180-degree peeling adhesive strength was measured at a speed of 300 mm / min using a tensile tester. 0.02 N / 25 mm or more and 2.50 N / 25 mm were evaluated as good adhesion and peeling properties.

[0200] Next, the surface of the adherend after the measurement of the 180-degree peel adhesive strength was visually observed, and the stain resistance was evaluated according to the following evaluation criteria.

[0201] (Evaluation Criteria)

[0202] ○: No contamination (no adhesive remains on the glass surface to such an extent that it can be visually confirmed)

[0203] ×: Contamination is present (adhesive remains on the glass surface to such an extent that it can be visually observed)

[0204] <Synthesis of crosslinkable functional group-containing polymer (A)>

[0205] [Synthesis example 1-1]

[0206] (Synthesis of Acrylic Polymer A-1)

[0207] Into a four-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube, and a condenser, 96 parts by mass of 2-ethylhexyl acrylate (2EHA) and 4 parts by mass of 4-hydroxybutyl acrylate (4HBA) were added, and 240 parts by mass of ethyl acetate as a solvent was added. Then, 0.15 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator was added while stirring under a nitrogen atmosphere, and the reaction was carried out at 67° C. for 8 hours. After the reaction, the mixture was cooled to obtain an acrylic polymer A-1 having a solid content concentration of 30.0% by mass.

[0208] [Synthesis Examples 1-2 to 1-8]

[0209] (Synthesis of Acrylic Polymers A-1 to A-8)

[0210] Except having set the compounding ratio of each monomer to the ratio shown in Table 1, it used the same method as Synthesis Example 1-1 to synthesize each acrylic polymer.

[0211] The composition and physical properties of each synthesized acrylic polymer are shown in the following Table 1. In addition, in Table 1, the abbreviations of monomers represent the following compounds. Mw (×10 4 ) means the value shown in Table 1 multiplied by 10 4 The obtained value is equivalent to Mw.

[0212] (Monomer containing a crosslinkable functional group (a1))

[0213] 4HBA: 4-Hydroxybutyl acrylate

[0214] HEA: Hydroxyethyl acrylate

[0215] ((Meth)acrylate monomer (a2))

[0216] 2EHA: 2-Ethylhexyl acrylate

[0217] iOA: Isooctyl acrylate

[0218] iNA: Isononyl acrylate

[0219] MA: Methyl acrylate

[0220] BA: Butyl acrylate [Table 1]

[0221]

[0222] <Synthesis of Polyisocyanate Composition (B)>

[0223] [Synthesis example 2-1]

[0224] (Synthesis of polyisocyanate component B-1)

[0225] In a four-necked flask equipped with a thermometer, a stirring blade and a reflux condenser, 100 parts by mass of HDI and 7.2 parts by mass of a trifunctional polycaprolactone polyol ("PLACCEL 303" (trade name) manufactured by Daicel Chemical Co., Ltd.) (equivalent to NCO / OH=17.1) were added under a nitrogen stream, and the temperature in the reactor was maintained at 90°C for 2.0 hours under stirring to carry out a urethanization reaction. Thereafter, the temperature in the reactor was maintained at 60°C, an isocyanurate-forming catalyst tetramethylammonium decanoate was added, and phosphoric acid was added to stop the reaction when the yield reached 50% by mass. After filtering the reaction solution, a thin film evaporator was used to remove unreacted HDI to obtain a polyisocyanate containing an isocyanurate group and an allophanate group. To 100 parts by weight of the obtained polyisocyanate, 0.91 parts by weight of polyester polyol ("PLACCEL 303" (trade name) manufactured by Daicel Chemical Co., Ltd.) was added (the amount was 2 mol% relative to 100 mol% of NCO% of the polyisocyanate), and 0.01 parts by weight of 2-ethylhexyl acid phosphate (JP-508T, manufactured by Johoku Chemical Industry Co., Ltd.) was added, and stirred at 95°C for 3.0 hours to obtain a polyisocyanate component B-1 containing an isocyanurate group, an allophanate group, and a carbamate group. The NCO content of the polyisocyanate component B-1 was 17.8% by mass, the weight average molecular weight was 5950, and the average number of isocyanate functional groups was 5.69. In consideration of operability, ethyl acetate was added to obtain a polyisocyanate composition having a solid content of 70%.

[0226] [Synthesis Examples 2-2 to 2-7]

[0227] (Synthesis of polyisocyanate components B-2 to B-7)

[0228] Except having made the kind and compounding ratio of a raw material into what is shown in Table 2, it used the same method as Synthesis Example 2-1, and synthesized each polyisocyanate component.

[0229] [Synthesis example 2-8]

[0230] (Synthesis of polyisocyanate component B-8)

[0231] In a four-necked flask equipped with a thermometer, a stirring blade and a reflux condenser, 100 parts by mass of HDI and 8.9 parts by mass of trimethylolpropane (hereinafter sometimes referred to as "polyol b3'-1") were added under a nitrogen stream, and the temperature in the reactor was maintained at 75°C for 5 hours under stirring to carry out a urethanization reaction. After filtering the reaction liquid, unreacted HDI was removed using a thin film evaporator to obtain a urethanate-type polyisocyanate (hereinafter sometimes referred to as "polyisocyanate component B-8").

[0232] [Synthesis example 2-9]

[0233] (Synthesis of polyisocyanate component B-9)

[0234] In a four-necked flask equipped with a thermometer, a stirring blade and a reflux condenser, 100 parts by mass of HDI was added under a nitrogen flow, the temperature in the reactor was maintained at 62°C under stirring, 0.095 parts by mass of trimethylbenzyl ammonium hydroxide was added, and the reaction was allowed to proceed for 4 hours. Thereafter, 0.02 parts by mass of phosphoric acid was added to stop the reaction when the conversion rate reached 38% by mass. After filtering the reaction solution, a thin film evaporator was used to remove unreacted HDI to obtain an isocyanurate type polyisocyanate (hereinafter sometimes referred to as "polyisocyanate component B-9").

[0235] [Synthesis example 2-10]

[0236] (Synthesis of polyisocyanate component B-10)

[0237] In a four-necked flask equipped with a thermometer, a stirring blade and a reflux condenser, 100 parts by mass of HDI and 7.3 parts by mass of a trifunctional polycaprolactone polyol ("OD-X-2733" (trade name) manufactured by DIC Corporation) (NCO / OH=17.2 equivalents) were added under a nitrogen stream, and the temperature in the reactor was maintained at 92°C for 2.0 hours under stirring to carry out a urethanization reaction. Thereafter, the temperature in the reactor was maintained at 60°C, an isocyanuration catalyst tetramethylammonium decanoate was added, and phosphoric acid was added to stop the reaction when the yield reached 50% by mass. After filtering the reaction solution, a thin film evaporator was used to remove unreacted HDI to obtain a polyisocyanate containing an isocyanurate group and an allophanate group. With respect to 100 parts by weight of the obtained polyisocyanate, 0.91 parts by weight of polyester polyol (manufactured by DIC Corporation, "OD-X-2733" (trade name)) and 0.01 parts by weight of 2-ethylhexyl acid phosphate (JP-508T, manufactured by Johoku Chemical Industry Co., Ltd.) were added, and stirred at 95°C for 3.0 hours to obtain a polyisocyanate component B-10 containing an isocyanurate group, an allophanate group and a carbamate group. The NCO content of the polyisocyanate component B-1 was 17.7% by mass, the weight average molecular weight was 5980, and the average number of isocyanate functional groups was 5.71. Considering the operability, ethyl acetate was added to obtain a polyisocyanate composition with a solid content of 70%.

[0238] [Synthesis example 2-11]

[0239] (Synthesis of polyisocyanate component B-11)

[0240] In a four-necked flask equipped with a thermometer, a stirring blade and a reflux condenser, 100 parts by mass of HDI and 12.0 parts by mass of a trifunctional polycaprolactone polyol ("PLACCEL 305" (trade name) manufactured by Daicel Chemical Co., Ltd.) (equivalent to NCO / OH=18.2) were added under a nitrogen stream, and the temperature in the reactor was maintained at 90°C for 2.0 hours under stirring to carry out a urethanization reaction. Thereafter, the temperature in the reactor was maintained at 60°C, an isocyanurate-forming catalyst tetramethylammonium decanoate was added, and phosphoric acid was added to stop the reaction when the yield reached 50% by mass. After filtering the reaction solution, a thin film evaporator was used to remove unreacted HDI to obtain a polyisocyanate containing an isocyanurate group and an allophanate group. To 100 parts by weight of the obtained polyisocyanate, 1.68 parts by weight of polyester polyol (manufactured by Daicel Chemical Co., Ltd., "PLACCEL 305" (trade name)) and 0.01 parts by weight of 2-ethylhexyl acid phosphate (JP-508T, manufactured by Johoku Chemical Industry Co., Ltd.) were added, and stirred at 95°C for 3.0 hours to obtain a polyisocyanate component B-11 containing an isocyanurate group, an allophanate group and a carbamate group. The NCO content of the polyisocyanate component B-11 was 17.12% by mass, the weight average molecular weight was 7790, and the average number of isocyanate functional groups was 5.64. In consideration of operability, ethyl acetate was added to obtain a polyisocyanate composition having a solid content of 70%.

[0241] [Synthesis example 2-12]

[0242] (Synthesis of polyisocyanate component B-12)

[0243] In a four-necked flask equipped with a thermometer, a stirring blade and a reflux condenser, 100 parts by mass of HDI and 18.0 parts by mass of a trifunctional polycaprolactone polyol ("PLACCEL 308" (trade name) manufactured by Daicel Chemical Co., Ltd.) (NCO / OH=19 equivalent) were added under a nitrogen stream, and the temperature in the reactor was maintained at 90°C for 2.0 hours under stirring to carry out a urethanization reaction. Thereafter, the temperature in the reactor was maintained at 60°C, an isocyanurate-forming catalyst tetramethylammonium decanoate was added, and phosphoric acid was added to stop the reaction when the yield reached 50% by mass. After filtering the reaction solution, a thin film evaporator was used to remove unreacted HDI to obtain a polyisocyanate containing an isocyanurate group and an allophanate group. With respect to 100 parts by weight of the obtained polyisocyanate, 2.57 parts by weight of polyester polyol (manufactured by Daicel Chemical Co., Ltd., "PLACCEL 308" (trade name)) and 0.01 parts by weight of 2-ethylhexyl acid phosphate (JP-508T, manufactured by Johoku Chemical Industry Co., Ltd.) were added, and stirred at 95°C for 3.0 hours to obtain a polyisocyanate component B-12 containing an isocyanurate group, an allophanate group and a carbamate group. The NCO content of the polyisocyanate component B-12 was 16.3% by mass, the weight average molecular weight was 8850, and the average number of isocyanate functional groups was 5.61. Taking into account the operability, ethyl acetate was added to obtain a polyisocyanate composition with a solid content of 70%.

[0244] [Synthesis example 2-13]

[0245] (Synthesis of polyisocyanate component B-13)

[0246] In a four-necked flask equipped with a thermometer, a stirring blade and a reflux condenser, 68 parts by mass of HDI, 32 parts by mass of IPDI and 3.24 parts by mass of trimethylolpropane (hereinafter sometimes referred to as "polyol b3'-1") were added under a nitrogen stream, and the temperature in the reactor was maintained at 83°C for 1 hour under stirring to carry out a urethanization reaction. Thereafter, tetramethylammonium decanoate, an isocyanurate-forming catalyst, was added, and phosphoric acid was added at a time point when the yield reached 43% by mass to stop the isocyanurate-forming reaction. Furthermore, after stirring at 88°C for 1.5 hours, the reaction solution was filtered, and unreacted HDI and IPDI were removed using a thin film evaporator to obtain an isocyanurate-type polyisocyanate (hereinafter sometimes referred to as "polyisocyanate B-13"). The obtained polyisocyanate B-13 had an NCO content of 18.8% by mass, a number average molecular weight of 3395, and an average number of isocyanate groups of 5.17. Taking the workability into consideration, ethyl acetate was added to obtain a polyisocyanate composition having a solid content of 70%.

[0247] The compositions and physical properties of the synthesized polyisocyanate components are shown in Tables 2 and 3 below. Mw (×10 3) means the values ​​shown in Table 2 to Table 3 multiplied by 10 3 The obtained value corresponds to Mw. In addition, in Tables 2 and 3, the polyols are the following compounds.

[0248] (Polyol (b2))

[0249] b2-1: trifunctional polycaprolactone polyol, manufactured by Daicel Corporation, trade name "PLACCEL 303", number average molecular weight 310

[0250] b2-2: trifunctional polycaprolactone polyol, manufactured by Daicel Corporation, trade name "PLACCEL 305", number average molecular weight 550

[0251] b2-3: trifunctional polycaprolactone polyol, manufactured by Daicel Corporation, trade name "PLACCEL 308", number average molecular weight 850

[0252] b2-4: trifunctional polycaprolactone polyol, OD-X-2733 manufactured by DIC Corporation, number average molecular weight 300

[0253] (Polyol (b3'))

[0254] b3'-1: Trimethylolpropane (TMP) [Table 2]

[0255]

[0256] [Table 3]

[0257]

[0258] <Evaluation of storage stability>

[0259] The storage stability was evaluated according to the following evaluation criteria.

[0260] ×: After the polyisocyanate was placed in a tank filled with an inert gas and placed in an environment at 23°C for one year, it gelled or its viscosity increased by 3.0 times or more of the initial value.

[0261] Δ: After the polyisocyanate was placed in a tank filled with an inert gas and placed in an environment at 23° C. for one year, the viscosity increase ratio was 2.0 times or more and less than 3.0 times the initial value.

[0262] ○: After the polyisocyanate was placed in a tank filled with an inert gas and placed in an environment at 23° C. for one year, the viscosity increase ratio was 1.5 times or more and less than 2.0 times the initial value.

[0263] ◎: After the polyisocyanate was placed in a tank filled with an inert gas and placed in an environment at 23°C for one year, the viscosity increase was less than 1.5 times the initial value.

[0264] <Manufacturing of Adhesive Resin Composition for Surface Protection Film>

[0265] [Example 1]

[0266] (Production of Adhesive Resin Composition S-a1 for Surface Protection Film)

[0267] To 100 parts by mass of the acrylic polymer A-1, 3.0 parts by mass of the polyisocyanate component B-1, 0.1 parts by mass of dioctyltin dilaurate (DOT: manufactured by Nitto Kasei Co., Ltd.: NEOSTANN 810) as a crosslinking accelerator, and ethyl acetate were added to obtain an adhesive resin composition S-a1 for a surface protection film having a solid content of 30% by mass.

[0268] [Examples 2 to 11 and Comparative Examples 1 to 4]

[0269] (Manufacture of Adhesive Resin Compositions S-a2 to S-a11 and S-b1 to S-b4 for Surface Protection Films)

[0270] Each adhesive resin composition for a surface protection film was prepared in the same manner as in Example 1 except that the types and blending ratios of the crosslinkable functional group-containing polymer (A) and the crosslinking agent component (B) were as shown in Tables 4 and 5.

[0271] Tables 4 and 5 show the composition and evaluation results of each adhesive resin composition for a surface protection film.

[0272] [Table 4]

[0273]

[0274] [Table 5]

[0275]

[0276] Examples 1 to 11 can obtain resin cured products with excellent quick-drying properties, hardness and strength, and adhesive compositions with excellent quick-drying properties and peeling properties. When made into surface protection films, they have good adhesion and peeling properties, and the contamination caused by the adhesive during peeling is improved.

[0277] The crosslinking agent components (B) of Comparative Examples 1 to 4 were inferior in quick-drying properties.

[0278] The adhesive resin composition of Comparative Example 2 was inferior in releasability and stain resistance.

[0279] Industrial Applicability

[0280] According to the present embodiment, there can be provided a resin cured product having excellent quick-drying properties, hardness and strength, an adhesive composition having excellent quick-drying properties and excellent releasability, a polyisocyanate composition having good followability to curved surfaces or uneven surfaces when made into a surface protection film, good adhesion and releasability, and improved contamination of the adherend by the adhesive during peeling; and a resin composition, a resin cured product, a resin cured film, an adhesive resin composition and a surface protection film obtained using the aforementioned polyisocyanate composition.

Claims

1. A polyisocyanate composition, which is a polyisocyanate derived from at least one di(tri)isocyanate (b1) selected from the group consisting of aliphatic di(tri)isocyanates and alicyclic di(tri)isocyanates and a difunctional or higher polyol (b2) having a number average molecular weight of 250 or more and 1000 or less, The ratio NCO / OH of the molar amount of the isocyanate group of the diisocyanate (triisocyanate) (b1) to the total molar amount of the hydroxyl group of the polyol (b2) is 2 or more and 30 or less, The polyisocyanate composition comprises isocyanurate groups, The average number of isocyanate functional groups is 5.1 or more and 7.0 or less, The weight average molecular weight Mw is 4,000 or more and 43,000 or less.

2. The polyisocyanate composition according to claim 1, wherein The polyisocyanate has an isocyanate group content (NCO%) of 13.5 mass % or more and 18.3 mass % or less in a state without containing a solvent.

3. The polyisocyanate composition according to claim 1 or 2, wherein The polyisocyanate contains allophanate groups.

4. The polyisocyanate composition according to claim 1 or 2, wherein The polyisocyanate contains allophanate groups and urethane groups.

5. The polyisocyanate composition according to claim 1 or 2, wherein The polyol (b2) contains at least one polyester polyol.

6. The polyisocyanate composition according to claim 1 or 2, wherein The polyol (b2) contains at least one polycaprolactone polyol.

7. The polyisocyanate composition according to claim 1 or 2, wherein The polyol (b2) contains at least one trifunctional or higher and tetrafunctional or lower polycaprolactone polyol. 8 . A resin composition comprising the polyisocyanate composition according to claim 1 or 2 and a compound having a crosslinkable functional group.

9. The resin composition according to claim 8, wherein The compound containing a crosslinkable functional group contains a hydroxyl group, an epoxy group, an oxetanyl group, a carboxyl group, an amino group or a thiol group.

10. A cured resin obtained by curing the resin composition according to claim 8 by light, electron beams or heat. 11 . A cured resin film, comprising the cured resin material according to claim 10 , wherein the cured resin film has a Koenig hardness at 23° C. of 20 times or more and 150 times or less and a maximum stress in a tensile test of 10 MPa or more.

12. An adhesive resin composition comprising the polyisocyanate composition according to claim 1 or 2 and a polymer containing a crosslinkable functional group, The glass transition temperature Tg of the polymer containing a crosslinkable functional group is not less than -75.0°C and not more than 0.0°C, The content of the polyisocyanate composition is 0.01 parts by mass or more and 15.0 parts by mass or less relative to 100 parts by mass of the crosslinkable functional group-containing polymer.

13. The adhesive resin composition according to claim 12, wherein The polymer containing a crosslinkable functional group is an acrylic polymer (A1) or a urethane polymer (A2), and the acrylic polymer (A1) is obtained by copolymerizing a monomer containing a crosslinkable functional group and a (meth)acrylate monomer having 1 to 18 carbon atoms at the end of the ester group.

14. The adhesive resin composition according to claim 13, wherein The content of the structural unit derived from the crosslinkable functional group-containing monomer is 0.01% by mass or more and 25% by mass or less relative to the total mass of the crosslinkable functional group-containing polymer.

15. The adhesive resin composition according to claim 12, wherein The weight average molecular weight of the polymer containing crosslinkable functional groups is 2.0×10 5 Above and 2.5×10 6 the following.

16. The adhesive resin composition according to claim 12, wherein The crosslinkable functional group-containing polymer contains one or more selected from the group consisting of a hydroxyl group, an epoxy group, an oxetanyl group, a carboxyl group, an amino group, or a thiol group.

17. A surface protection film comprising a plastic film, and an adhesive layer on one or both sides of the plastic film, The adhesive layer is a cured product of the adhesive resin composition according to claim 12 .

18. The surface protection film according to claim 17, wherein The adhesive layer has a thickness of 1 μm or more and 1000 μm or less.

19. The surface protection film according to claim 17, wherein The gel fraction calculated as follows is 90.0 mass % or more and 100.0 mass % or less: The adhesive resin composition is coated on a release-treated polyethylene terephthalate film having a thickness of 38 μm, dried at 136°C for 3 minutes to cure it, and then stored at 23°C, 50% RH for 7 days. The adhesive layer having a thickness of 20 μm thus obtained is peeled off from the release film, stored at 23°C, 50% RH for 7 days, and then wrapped with a mesh sheet, immersed in ethyl acetate at 23°C for 1 week, taken out, and dried at 120°C for 2 hours, thereby calculating the gel fraction.

20. The surface protection film according to claim 17, wherein The Young's modulus in the tensile test performed as follows is 0.05 N / mm 2 Above and 0.60N / mm 2 the following: The adhesive resin composition is coated on a polyethylene terephthalate film with a thickness of 38 μm and subjected to a peeling treatment, and after being cured by drying at 136° C. for 3 minutes, it is stored at 23° C. and 50% RH for 7 days. The adhesive layer with a thickness of 20 μm thus obtained is laminated in a manner to have a thickness of 200 μm, cut into a layer with a width of 10 mm and a length of 40 mm, and then peeled off from the polyethylene terephthalate film with a peeling treatment. The peeled adhesive layer is set in a tensile testing machine in a manner such that the distance between chucks becomes 10 mm, and the tensile test is carried out at a speed of 300 mm / min at 23° C.

21. The surface protection film according to claim 17, wherein The 180 degree peel adhesion measured as follows is 0.02 N / 25 mm or more and 2.50 N / 25 mm or less: The adhesive resin composition is coated on a polyethylene terephthalate film with a thickness of 25 μm, dried at 136°C for 3 minutes to cure it, and then stored at 23°C and 50% RH for 7 days. A surface protection film having an adhesive layer with a thickness of 20 μm, a width of 25 mm and a length of 100 mm is attached to a glass adherend, and is reciprocated and pressed once using a 2 kg roller. After aging at 23°C for 30 minutes, the 180 degree peeling adhesive strength is measured at 23°C and a speed of 300 mm / min.

Citation Information

Patent Citations

  • Acrylic polyol and composition for two-pack urethane resin coating containing it

    JP1989261409A

  • Weatherable paint composition

    JP1991006273A

  • Adhesive composition and optical member surface protective film

    JP2017128636A

Cited By

  • High-functionality polyisocyanate composition and preparation method thereof

    CN121673519A